2010
DOI: 10.1001/jama.2010.563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Azithromycin on Pulmonary Function in Patients With Cystic Fibrosis Uninfected With <emph type="ital">Pseudomonas aeruginosa</emph><subtitle>A Randomized Controlled Trial</subtitle>

Abstract: clinicaltrials.gov Identifier: NCT00431964.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
199
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(213 citation statements)
references
References 31 publications
9
199
1
4
Order By: Relevance
“…Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks. Azithromycin treatment did not improve pulmonary function, suggesting that the beneficial effect of azithromycin in CF is mainly due to its activity against P. aeruginosa [36]. However, it should be noted that the vast majority of the recruited patients had very good lung function (mean forced expiratory volume in 1 s (FEV1) nearly 100% predicted in both groups), thus reducing the chance of improving lung function with any intervention.…”
Section: Cystic Fibrosismentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks. Azithromycin treatment did not improve pulmonary function, suggesting that the beneficial effect of azithromycin in CF is mainly due to its activity against P. aeruginosa [36]. However, it should be noted that the vast majority of the recruited patients had very good lung function (mean forced expiratory volume in 1 s (FEV1) nearly 100% predicted in both groups), thus reducing the chance of improving lung function with any intervention.…”
Section: Cystic Fibrosismentioning
confidence: 93%
“…The possibility that macrolides might modify the neutrophilic inflammatory response in CF was first investigated in the early 2000s. Since then, a number of clinical trials have confirmed their beneficial effects both in adults and children [31][32][33][34][35][36][37]. Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…The presence of specific signs and symptoms were collected at the time of prescribing a new antibiotic to evaluate whether the event qualified as a study-defined pulmonary exacerbation [27,28]. In brief, an exacerbation was defined as receiving new antibiotic treatment plus 1 or 2 of the 2 major criteria ( 10% decrease in FEV 1 from 6-month baseline, or oxygen saturation <90%, or 5% decline) or 2 or more of the 8 minor criteria (new or increased: cough, fatigue, chest congestion or sputum, respiratory symptoms or adventitial sounds; decreased: activity, appetite, or weight).…”
Section: Data Collectionmentioning
confidence: 99%
“…The mechanism of macrolides effect on CF lung disease is unknown. The possibility that macrolides might modify the neutrophilic inflammatory response in CF was investigated and their beneficial effects have been confirmed in a number of clinical trials both in adults and children [12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%